Cooperation between the natives and chinese community in Sabah (1945-1963) : an analytical study - Rosdianah binti Yacho (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
Tolerance and responsibility are important among society to establish a good quality of life. This study explores the situation in Sabah between 1945-1963 by giving special attention to the cooperation between the natives and the Chinese immigrant community. The cooperation focuses on the fields of socio-economic and political fields. It shows the significance of cooperation between both groups of people in the development of the region after World War II. Before the war, the situation in Sabah could be considered as developed. However, everything changed after the region faced heavy destruction through the war. A lot of efforts had been placed to re-establish the region. This study will then examine how the cooperation among the people can be established. Cooperation is one of the core elements for any countries or nations to create a civilization or development. It cannot be denied that cooperation is not an easy thing to bring forward in a multi-cultural society. Sabah consists of different groups of people and, as a result, cooperation became a big challenge to develop. Therefore, this study investigates the responses of the natives and the Chinese community on this. In this study, primary and secondary sources were used in searching for the information regarding this topic. The findings indicate that cooperation can occur because of the people and the situation of the land.